Integration of Agrarian Literacy in Citizenship Education - Andari, Dwi Wulan Titik; Mujiburohman, Dian Aries (Jurnal Pendidikan Progresif, 2025)
Integration of Agrarian Literacy in Citizenship Education. Objective: This study aims to formulate an integration model of land literacy within social education to enhance students’ critical awareness and serve as a preventive strategy against agrarian conflict in Indonesia. Method: This qualitative literature analysis draws on Paulo Freire's critical pedagogy to combine recent empirical findings with agrarian policy advances. Finding: Apart from unequal land ownership, the study shows those agrarian conflicts result from young people's ignorance of land rights, legal procedures, and history. Civic education in schools also emphasizes excessive memorization and fails to connect with students' local realities. The current curriculum does not address local agrarian issues, and teaching methods are mostly one-sided, failing to encourage critical thinking or active participation from students. To address this, the study suggests a model for agrarian literacy that includes three key components: (1) a curriculum that covers local agrarian topics like customary rights, land disputes, and agrarian law; (2) engaging learning methods like project-based learning and real-life case studies of land conflicts; and (3) partnerships with organizations like the National Land Agency, traditional institutions, and non-governmental organizations in the agrarian field. Conclusion: Agrarian literacy is an important citizenship competency that helps form citizens who are legally aware, sensitive to social justice, and capable of actively resolving land conflicts. Therefore, agrarian literacy needs to be systematically integrated into the national education framework. Keywords: land literacy, civic education, agrarian conflict, critical pedagogy, civic engagement.